The Associations between Perceived Parenting Styles, Empathy, and Altruistic Choices in Economic Games: A Study of Chinese Children - Guo, Qingke; Feng, Linlin (Frontiers in Psychology, 2017)
Parenting styles are critical for fostering children’s empathy and prosociality. Yet these relations haven’t been well established for Chinese children, and the underlying mechanisms were seldom explored. Drawing upon parental acceptance-rejection theory and empathy-altruism hypothesis, the objective of this study was to investigate the relationships between perceived parenting styles and altruistic behavior of children, and the intervening role of children’s empathy and the moderating role of in-group and out-group conditions. What is novel about this study is that it contains both survey data and experimental data. Four hundred and ninety-four children (Mage = 8.92 years) completed four simple binary-choice dictator games which are widely used in the study of other-regarding preferences (concerns for the interests of others). These children also reported their perceived parenting styles. And children’s empathy was reported by their mothers. Each child’s altruism score, which was used in the subsequent analyses, was derived from the altruistic choices in these games. Mediation analyses indicated that, when age and gender were controlled for, maternal and paternal emotional warmth were positively associated with children’s altruism via children’s empathy, while maternal and paternal rejection were negatively associated with children’s altruism via children’s empathy. Multi-group analyses showed that the influences of perceived parenting styles on children’s altruistic behavior via children’s empathy were consistent for in-group and out-group conditions. These findings suggest that enhancing parental emotional warmth and reducing parental rejection may foster children’s empathy, which in turn promote children’s altruism. Limitations and future directions of this study were also discussed.